[tex]\displaystyle\bf\\f(x)=x(\sqrt{x} +1) \ \ \ , \ \ \ x_{0} =1\\\\\\f'(x)=x'\cdot(\sqrt{x} +1)+x\cdot(\sqrt{x} +1)'=1\cdot (\sqrt{x} +1)+x\cdot\frac{1}{2\sqrt{x} }=\\\\\\=\sqrt{x} +1+\frac{x}{2\sqrt{x} }=\sqrt{x} +1+0,5\sqrt{x}=1,5\sqrt{x} +1\\\\\\f'(x_{0})=f'(1)=1,5\cdot\sqrt{1} +1=1,5+1=2,5\\\\\\Otvet \ : \ f'(1)=2,5[/tex]
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
[tex]\displaystyle\bf\\f(x)=x(\sqrt{x} +1) \ \ \ , \ \ \ x_{0} =1\\\\\\f'(x)=x'\cdot(\sqrt{x} +1)+x\cdot(\sqrt{x} +1)'=1\cdot (\sqrt{x} +1)+x\cdot\frac{1}{2\sqrt{x} }=\\\\\\=\sqrt{x} +1+\frac{x}{2\sqrt{x} }=\sqrt{x} +1+0,5\sqrt{x}=1,5\sqrt{x} +1\\\\\\f'(x_{0})=f'(1)=1,5\cdot\sqrt{1} +1=1,5+1=2,5\\\\\\Otvet \ : \ f'(1)=2,5[/tex]